Identification of bioactive lipids associated with osteoarthritis pain and pathology through targeted lipidomic analyses - Turnbull, James (2023)
Osteoarthritis (OA) is the leading cause of disability in the older population and is characterised by the degradation of the affected joint and development of chronic pain. There are currently no approved treatments that halt or reverse the joint pathology, and current treatments for associated pain are unsuitable for long-term treatment. There is also the need to identify those at high risk of developing OA that would benefit from early intervention. The oxylipins are oxidised lipid metabolites of polyunsaturated fatty acids (PUFAs), which play a central role in the regulation of the inflammatory response. They have also been reported to be involved in pain signalling and so present as attractive potential biomarkers and therapeutic targets for OA. This thesis aimed to develop methods to quantify a panel of pro- and anti-inflammatory oxylipins in biological samples using liquid chromatography-mass spectrometry (LC-MS/MS); and apply this method to clinical and pre-clinical studies involving participants with OA and animal models of the disease. The LC-MS/MS method developed covered the omega-3 and omega-6 PUFAs and many of their metabolites including eicosanoids, docosanoids, and endocannabinoids. The method was optimised over a 25 minute run time which allowed good separation of isomeric compounds and was sensitive into the picomolar range. Application of the method to plasma and serum collected from healthy volunteers (n=10) found significantly high levels of many oxylipins in serum compared to plasma. In a longitudinal study of healthy young adults who had suffered acute knee injury and are at high risk of developing OA in the future (n=47), levels of omega-3 PUFAs and their metabolites were significantly higher immediately after injury compared to later time points and controls. The opposite was observed for pro-inflammatory eicosanoids, which were significantly lower immediately after injury compared to later time points. At two years after injury, levels of the DHETs (metabolites of soluble epoxide hydrolase (sEH)) were associated with worse knee symptom scores. Measuring the oxylipins in a community cohort of people with varying levels knee pain and OA (n=154) identified metabolites of LOX and CYP450 as being associated with radiographic OA. Levels of 8,9-EET, 14,15-DHET, 12-HpETE, and AEA were also associated with measures of self reported pain. Stratification of participants based pain and radiographic OA scores showed significantly higher levels of several EETs, 14- & 17-HDHA, and the HETEs. Baseline levels of 8,9-EET, 5-HETE, and 5,6-DHET were also associated with pain scores collected at 3 years follow-up. Using the destabilisation of the medial meniscus (DMM) model of OA, oxylipins were measured at 4, 8, and 12 weeks post model induction. Levels of prostaglandins, HETEs, EETs, and 12-HpETE were associated with synovitis and cartilage degradation scores at 4 and 8 weeks post-surgery; and levels of 17-HDHA were associated with less pain at 16-weeks post-injury. Targeting the sEH enzyme in the DMM model using an inhibitor called TPPU showed complete reversal of pain behaviour, decreased levels of DHETs, and increased EET:DHET ratios. Levels of 8,9-DHET were also associated with worse pain scores. During the COVID-19 pandemic the method was repurposed and serum from n=50 patients were measured for their oxylipin profile. Levels of both pro- and anti-inflammatory oxylipins were significantly higher in COVID-19 patients compared to controls. There were significant positive correlations between specialised pro-resolving mediators (SPMs), pro-inflammatory bioactive lipids, and anti-spike antibody binding. Levels of linoleic acid and 5,6-DHET were significantly lower in SARS-CoV-2 patients who died. These studies suggest a role of the oxylipins in OA pathology and associated pain phenotypes, and identify potential targets for therapeutic intervention for both joint pathology and pain. Through validation in replication cohorts, there is also the potential of using key oxylipins identified here, to predict future pain score. Future studies should look at the difference between serum/plasma and synovial fluid profiles of oxylipins in people with OA which may gave further mechanistic insight into their role in the pathogenesis of OA.